Learning Innovation at PTAI (Analysis ofNeeds for Implementing LearningModelsResearch-based Learning) - Hajriana Hajriana (Education Studies and Teaching Journal (EDUTECH), 2024)
Being a university that implements research-based education is one of the missions ofIslamic Religious Education study program at PTAI East Kalimantan. It will be difficult torealize if students have lack abilities to do research. This study aims to analyze theimportance of learning inovations by applying research-based learning and studentcharacteristic of PAI study program by qualitative method. The results showed thatimplementation of learning in Islamic Religious Education study program at PTAI did notsupport the improvement of student research abilities, so it needed to be supportedthrough learning innovations that were integrated research activities in the formdevelopment and application of research-based learning that was adjusted to thecharacteristics of the learners were millennial and part-time students.